การศึกษาเปรียบเทียบเงินสำรองค่าสินไหมทดแทนโดยวิธีบันไดลูกโซ่และการปรับเส้นโค้งปัจจัยความเสียหายพัฒนา - ณัฐพงษ์ ปู่ทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The aim of this research is to compare loss modeling in actuarial framework between Chain-Ladder model (the classical method), and LDF Curve Fitting by comparing expected reserve, standard deviation of reserve and coefficient of variation (CV) of reserve from each models in various simulated scenarios. The results show that the Chain-Ladder model still works well in most scenarios because its coefficient of variation is lower than LDF Curve Fitting. Chain-Ladder model should be the main method in calculation of the reserve. However, in situations where the data has the loss development factor curve (LDF curve) resembles concave curve or S-shaped with the logarithm of loss development factors in each column are high and sample size is small, the Weibull LDF Curve Fitting should be used because the coefficient of variation of the reserve is lower than the Chain-Ladder model.